Microbubbles composition optimisation for ferritin tethering: ensuring activity and structure retention of ferritin - Hanna Mariah Binte Mohamed Rizal (Nanyang Technological University, 2024)
Atherosclerosis remains a leading cause of morbidity and mortality on a global scale, highlighting the urgent need for advanced diagnostic techniques to monitor its progression closely. Magnetic resonance imaging (MRI) is a non-invasive imaging modality for visualizing atherosclerotic plaques with enhanced sensitivity and specificity using contrast agents. Ferritin, a nano protein that stores iron, has emerged as a promising MRI contrast agent due to its ability to accumulate in atherosclerotic lesions. However, efficient delivery of ferritin to the targeted site remains a challenge. Microbubbles, which are gas-filled lipid vesicles have garnered significant attention as carriers for ferritin-based MRI contrast agents in diagnosing atherosclerosis. Tethering of ferritin to microbubbles is proposed to accelerate the transportation of MRI contrast agents to the targeted site and thus enables faster MRI contrast enhancement. Thus, this study will involve a comparative investigation of whether microbubbles are capable carriers of ferritin. Furthermore, recent advancements in the design and engineering of microbubbles will be examined and leveraged for enhanced stability and structural integrity. Future directions and challenges in translating microbubbles-based ferritin delivery systems into clinical applications, including optimization of formulation and safety profiles, will be discussed in the later section of this report.